A Relational Account of the Spanish Noun Phrase - Gil, Jose Maria (2016)
I aim to show that the Spanish Noun Phrase is a network of relationships. More specifically, I aim to show that the structure and the function of the Spanish Noun Phrase can be described and explained by Lamb's relational networks. In fact, relational networks notation allow us not only to describe the Spanish Noun Phrase, but also to elucidate some features that are not elucidated by a description in words or in linear notation: they allow us to understand that the choice of a concrete grammatical structure is determined by the choice of the meanings that will be communicated. The Spanish Noun Phrase is a complex syntactic structure whose account in relational terms helps us to understand how the necessity of expressing certain meanings determines lexicogrammatical choices. Within the linguistic network, the nections at the lexicogrammatical level are connected to certain nections at the sememic level, and the activation of such sememic nections is what determines the activation of certain lexicogrammatical nections. Since relational networks show that grammatical structures are determined by meaning, the account developed in this paper reinforces the idea that Relational Network Theory is compatible with Systemic Functional Linguistics.